Systemic Approach to Malignant Pleural Mesothelioma: What News of Chemotherapy, Targeted Agents and Immunotherapy?. Issue 1 (January 2016) - Signorelli, Diego; Macerelli, Marianna; Proto, Claudia; Vitali, Milena; Cona, Maria Silvia; Agustoni, Francesco; Zilembo, Nicoletta; Platania, Marco; Trama, Annalisa; Gallucci, Rosaria; Ganzinelli, Monica; Pelosi, Giuseppe; et al.
Malignant pleural mesothelioma is a rare cancer with a cause-effect relationship to asbestos exposure. The prognosis is poor and chemotherapy seems the best treatment option. In the last two decades a deeper understanding of mesothelioma carcinogenesis and invasiveness mechanisms has prompted research efforts to test new agents in patients with malignant pleural mesothelioma, but the results have been modest. Attractive preclinical data disappointed in subsequent experimental phases. Other promising agents failed to improve patient outcomes due to high toxicity. Interesting suggestions have come from preliminary data on immunotherapy. Several trials are ongoing and the results are eagerly awaited. The aim of this review is to discuss the most recent news on systemic therapy for advanced malignant pleural mesothelioma.